2016
DOI: 10.1097/pcc.0000000000000943
|View full text |Cite
|
Sign up to set email alerts
|

Association of Extracorporeal Membrane Oxygenation Support Adequacy and Residual Lesions With Outcomes in Neonates Supported After Cardiac Surgery*

Abstract: Our data suggest that clearance of lactate is an important therapeutic target for patients cannulated to extracorporeal membrane oxygenation. In addition, timely identification of residual lesions and expedient interventions on those lesions may improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…First, the finding that 40% of early-ECMO patients had residual anatomic lesions that were corrected by intervention using catheterization or surgery highlights the importance of patient assessment with early TEE and/or cardiac catheterization if patients are not progressing as expected. The safety and importance of TEE and cardiac catheterization to identify and manage residual lesions, particularly in patients on ECMO, has been noted by others [2228]. Kato et al found that patients who received catheterization within 48 h after ECMO cannulation had fewer respiratory complications and better 30-day survival than those who had later catheterization [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the finding that 40% of early-ECMO patients had residual anatomic lesions that were corrected by intervention using catheterization or surgery highlights the importance of patient assessment with early TEE and/or cardiac catheterization if patients are not progressing as expected. The safety and importance of TEE and cardiac catheterization to identify and manage residual lesions, particularly in patients on ECMO, has been noted by others [2228]. Kato et al found that patients who received catheterization within 48 h after ECMO cannulation had fewer respiratory complications and better 30-day survival than those who had later catheterization [27].…”
Section: Discussionmentioning
confidence: 99%
“…Agarwal et al found that earlier detection of residual lesions during the first 3 days of ECMO (compared with later detection) was associated with a higher rate of decannulation and survival to hospital discharge [23]. Howard et al found that the time to diagnosis or correction of residual lesions was significantly shorter in neonatal cardiac ECMO survivors (1 vs 2 days, p  = 0.02) [28]. Second, the variables we found as independently predictive of early ECMO may not be easily modifiable.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated lactate levels are often a marker of inadequate tissue oxygenation and inability to clear lactate while receiving ECMO may indicate ongoing oxygen debt. Among neonatal and pediatric patients undergoing cardiac ECMO, prior studies have shown elevated lactate more than 24–72 hours post-cannulation is associated with increased mortality (18, 19) and that the time required for lactate to normalize (<2 mmol/L) on ECMO is associated with worse cognitive outcome in survivors (20). A recent study in adults receiving VV ECMO for acute respiratory distress syndrome found increased mortality among those who failed to clear lactate within the first 72 hours of ECMO (21).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric cardiac surgical programs routinely use extracorporeal membrane oxygenation (ECMO) to rescue surgical patients with cardiopulmonary failure, and predictors of ECMO support in these patients have been well documented . However, predictors of ECMO support in adults after CHD surgery have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Pediatric cardiac surgical programs routinely use extracorporeal membrane oxygenation (ECMO) to rescue surgical patients with cardiopulmonary failure, and predictors of ECMO support in these patients have been well documented. [7][8][9][10][11] However, predictors of ECMO support in adults after CHD surgery have not been previously reported. Because adult patients are likely to be active participants in their medical decision making, identifying patients who are at increased risk of requiring ECMO support is important for presurgical discussion and planning.…”
Section: Introductionmentioning
confidence: 99%